Faktor yang Berhubungan dengan Kepatuhan Pengobatan Pasien Hemodialisa di Rumah Sakit H. Adam Malik Medan - Nurhayati Syihab; Mappeaty Nyorong; Nuraini Nuraini (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
Hemodialysis is a treatment that is carried out for patients with chronic kidney failure in order to survive, however, this action has side effects on the patient's physical and psychological condition, hemodialysis is a replacement treatment for patients with terminal stage chronic kidney failure, so that kidney function is replaced with a tool called dyalizer, in this dyalizer the process of transferring dissolved substances in the blood into the dialysis fluid and vice versa. The research method is an analytical survey with a cross sectional approach. The sample used is total sampling where the entire population is the research sample, namely all patients with pulmonary tuberculosis. The statistical test used is the chi-square test and multiple logistic regression. The results showed that the factors related to adherence to treatment for hemodialysis patients were knowledge (p= 0.000 < 0.005), access to health facilities (p = 0.031 < 0.05), family support (p = 0.001 <0.05), and support from health workers (p = 0.011). <0.05). Multivariate analysis showed that the factors that influenced adherence to treatment were knowledge (p = 0.002 < 0.05) and family support (p = 0.005 < 0.05). And the most dominant factor influencing is the influence of family support factors (p = 0.016 < 0.005) with an Exp (B) value of 13,761. Bad public health behavior can occur due to a lack of public knowledge and understanding of the disease and its risks so that the community does not know how to act so that the disease is not more at risk. To improve adherence to treatment for hemodialysis patients, it is necessary to increase knowledge and good support from the family, by intervening through education related to hemodialysis and approaches with the patient's family.